Pengaruh Booklet PEMANTIK dalam Meningkatkan Pengetahuan dan Sikap Kader Pemantau Jentik Sebagai Upaya Pengendalian Demam Berdarah Dengue (DBD) Di Wilayah Kerja Puskesmas Sako Palembang - Regista Lidyani; Priyadi, Priyadi; Intan Kumalasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus, transmitted through the bite of a mosquito vector of the species Aedes egypti or Aedes albopictus. The incidence of DHF increases during the rainy season when there are many stagnant waters which are breeding grounds for mosquitoes. Integrated Vector Control is an effective risk management as an effort to eradicate mosquito nests continuously and continuously with the 1 house 1 jumantik movement program. One of the efforts made to optimize community participation in DHF control is empowering school children to become Jumantik-PSN School cadres by increasing students' knowledge and attitudes through the jumantik booklet. The research objective was to determine the effect of booklets in increasing the knowledge and attitudes of Cadres in controlling Dengue Hemorrhagic Fever. The research method uses a pre-experiment with a one group pre-post test design, data collection techniques by filling out a knowledge and attitude questionnaire. This research was conducted in March-May 2023. The study population was all school jumantik_PSN cadres in the working area of ​​the Sako Health Center, with a total sample of 57 respondents obtained using the stratified random sampling technique. The results of data analysis using the Wilcoxon Test showed significant differences in pretest and posttest values after being educated using the Jumantik booklet with p (0.000), it can be concluded that the booklet media is an effective and informative medium in increasing the knowledge and attitudes of Jumantik-PSN cadres for school children as an effort to control dengue hemorrhagic fever in schools.